Does classroom-based Crew Resource Management training improve patient safety culture? A systematic review. (4th April 2014) - Verbeek-van Noord, Inge; de Bruijne, Martine C; Zwijnenberg, Nicolien C; Jansma, Elise P; van Dyck, Cathy; Wagner, Cordula
Aim: To evaluate the evidence of the effectiveness of classroom-based Crew Resource Management training on safety culture by a systematic review of literature. Methods: Studies were identified in PubMed, Cochrane Library, PsycINFO, and Educational Resources Information Center up to 19 December 2012. The Methods Guide for Comparative Effectiveness Reviews was used to assess the risk of bias in the individual studies. Results: In total, 22 manuscripts were included for review. Training settings, study designs, and evaluation methods varied widely. Most studies reporting only a selection of culture dimensions found mainly positive results, whereas studies reporting all safety culture dimensions of the particular survey found mixed results. On average, studies were at moderate risk of bias. Conclusion: Evidence of the effectiveness of Crew Resource Management training in health care on safety culture is scarce and the validity of most studies is limited. The results underline the necessity of more valid study designs, preferably using triangulation methods.